1977
DOI: 10.1093/infdis/135.6.970
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of 5-Fluorocytosine as Measured by Disk Diffusion Susceptibility Testing

Abstract: The susceptibilities of 216 isolates of pathogenic and commensal yeasts to 5-fluorocytosine were tested by a disk diffusion technique with use of 1- and 10-microgram disks. Minimal inhibitory concentrations (MICs) were determined by an agar dilution procedure with yeast morphology agar, pH 5.0, supplemented with 0.25 mg of thiamine/dl. Zones of inhibition produced by the two disks were correlated with paired MIC values. An MIC of 16 micrograms/ml, the upper limit of probable clinical susceptibility, correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In the United States, using this same definition, we found a resistance rate of 11.5 to 15.5% in four geographic centers and 35% at the fifth. This is comparable to the 21% rate of resistance reported in Montreal, Canada, by Auger et al (1) Earlier disk diffusion studies (12,19) showed better correlation between zone size and 48-h MICs than that reported here. Hutlet (11), however, noted a poor correlation between zone size and 24-h MICs.…”
Section: Discussionsupporting
confidence: 89%
“…In the United States, using this same definition, we found a resistance rate of 11.5 to 15.5% in four geographic centers and 35% at the fifth. This is comparable to the 21% rate of resistance reported in Montreal, Canada, by Auger et al (1) Earlier disk diffusion studies (12,19) showed better correlation between zone size and 48-h MICs than that reported here. Hutlet (11), however, noted a poor correlation between zone size and 24-h MICs.…”
Section: Discussionsupporting
confidence: 89%
“…Disk Agar Diffusion (DAD) method [17] was used in this study. The plates were prepared by pouring about 15 mL of molten Sabouraud dextrose agar into sterile petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Such primary resistance to 5-FC has been seen in varying degrees with a relatively wide range of clinical isolates of various fungus species. With Candida spp., a number of reports were published from 1971 to 1982 (8, 13, 16,34,36,41,42,50,59,64,68,69,93,107,115,132,138,151,152,154,156,164,165,173,175,176). In those reports, the highest levels in the incidence of resistant isolates of C. albicans recorded so far were 37.2% found among 175 strains in Canada (93), and 25.8% found in the study of 58 isolates in the United States (175); intermediate levels, e.g.…”
Section: Flucytosine Resistancementioning
confidence: 99%